DELAY IN DIAGNOSING ALDOSTERONE-PRODUCING ADENOMA: CAN WE DO BETTER? - G, Kian Guan; Z, Miza Hiryanti; S, Saiful Shahrizal (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Incidence of primary hyperaldosteronism is rising due to better detection and awareness among physicians. However, there is delay in patients receiving appropriate care. In these 2 case-series of aldosterone-producing adenoma, we summarized the key events until tumour removal. METHODOLOGY All case notes of new patients attending endocrine clinic Hospital Tengku Ampuan Afzan from 1st January 2017 till 1st May 2019 were screened. Cases fulfilling the diagnosis of primary hyperaldosteronism were included. Key events were reviewed and summarized. RESULTS Case 1 is a lady with hypertension for 7 years and hypokalaemia for 3 years. ARR done in December 2016 was positive. She was seen in endocrine clinic about 2 months later, saline suppression test (SST) was done after 2 weeks, but CT of the adrenals was done 3 months after SST. She was referred 3 months later to endocrine Hospital Putrajaya where adrenal vein sampling (AVS) was done. Results of AVS was made available after 1-month. She was referred to an endocrine surgeon after 6 weeks and operated 2 months later. Total time from ARR to table was 13 months. Case 2 is another lady with hypertension and hypokalaemia for 15 years. ARR was done in April 2017. She was only referred to endocrine clinic after 3 months. SST was done 6 weeks later, but the results were only reviewed after 3 months. CT of the adrenals was done after 3-month time. She was referred to endocrine Hospital Putrajaya for AVS which was done after 2 weeks. Finally, she was operated 6 months after AVS. Total time from ARR to table was 18 months. CONCLUSION There is delay from screening until definitive treatment. The process can be improved if there is proper diagnostic workflow for similar cases. Proper result-tracing and faster scans are desired. With improved diagnosis speed, hopefully there will be faster action to benefit the patients.